Effects of occasional tillage on soil physical and chemical properties and weed infestation in a 10-year no-till system - Diop, Massamba; Beniaich, Adnane; Cicek, Harun; Ouabbou, Hassan; El Gharras, Oussama; Tanji, Abbès; Bamouh, Ahmed; Dahan, Rachid; Zine El Abidine, Aziz; El Gharous, Mohamed; El Mejahed, Khalil (Frontiers in Environmental Science, 2024)
Few studies have investigated how one-time targeted tillage of long-term no-till fields impacts topsoil properties and weed dynamics. An on-farm trial was implemented in 2020 to test the effects of occasional tillage (OT) in Morocco with a long-term no-tillage (NT) system and rainfed field crops: durum wheat (Triticum durum), faba bean (Vicia faba minor), and chickpea (Cicer arietinum). Four treatments were established, namely, continuous NT with crop residues maintained (“NT + residue”); continuous NT with crop residues not maintained (“NT-residue”); shallow inversion tillage (“shallow OT”); and deep non-inversion tillage (“deep OT”). We assessed the effect of these treatments on soil physical and chemical properties in 0–10 and 10–20 cm soil depths after crop harvest of the 2020–2021 (year 1) and 2021–2022 (year 2) growing seasons corresponding to 1 and 2 years after OT, respectively. In addition, we evaluated the effect of the treatments on weed populations and the effect of the legume crop rotated with wheat on soil nitrogen (N) and weed density. In year 1, deep OT reduced the water content at field capacity and available water capacity at 0–10 cm compared to continuous NT; the cation-exchange capacity (CEC) under deep OT was lower than in NT-residue and NT + residue at 0–10 cm and 10–20 cm, respectively. Furthermore, deep OT increased ammonium-N (NH4-N) at 0–10 and 10–20 cm compared to NT + residue but reduced exchangeable potassium (K) at 10–20 cm depth compared to NT-residue. In year 2, shallow OT had lower total porosity at 10–20 cm than NT + residue, while shallow and deep OT recorded higher water-stable aggregates at 0–10 cm than NT + residue; at 10–20 cm, deep OT recorded lower CEC than NT + residue. However, deep OT had higher nitrate-N (NO3-N) and available sulfur (S) than NT-residue at 10–20 cm. Occasional tillage did not significantly affect 10 out of 19 of the soil properties evaluated, including soil organic matter (SOM), in all the years and did not help reduce the stratification of soil nutrients in NT. In year 1, 50 days after OT, deep OT reduced the weed density by 46% compared to NT + residue, while in year 2, 406 days after OT, shallow OT reduced weed density by 53% compared to NT-residue. Regarding the effect of the legume rotated with wheat, faba bean appeared to be the better preceding or following wheat crop as it resulted in higher residual soil mineral N and lower weed infestation than chickpea.